2017
DOI: 10.1111/jphp.12766
|View full text |Cite
|
Sign up to set email alerts
|

Asn194Lys mutation in RVG29 peptide increases GFP transgene delivery by endocytosis to neuroblastoma and astrocyte cells

Abstract: The complexes pGL-mRVG29 and pGL-RVG29-KP have specificity for transfecting astrocytes and SH-SY5Y cells. The karyophilic capacity of this new mRVG peptide render it promising candidate to act as gene delivery vector into the brain cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…Although the delivery of RNA molecules to the brain with RVG‐9R has already been described (Kumar et al, ), in this study we proved that the modification of an amino acid (mRVG‐9R) is more efficient in the delivery of charge molecules than the RVG‐9R peptide as we published previously (Villa‐Cedillo et al, ). And now we have demonstrated its transfection capacity in vivo.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Although the delivery of RNA molecules to the brain with RVG‐9R has already been described (Kumar et al, ), in this study we proved that the modification of an amino acid (mRVG‐9R) is more efficient in the delivery of charge molecules than the RVG‐9R peptide as we published previously (Villa‐Cedillo et al, ). And now we have demonstrated its transfection capacity in vivo.…”
Section: Discussionsupporting
confidence: 83%
“…In our previous report, we confirmed successful cellular transfection of neuroblastoma cells and astrocytes i n vitro using mRVG‐9R complexes (Villa‐Cedillo et al, ).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Interestingly, we showed that a peptide, composed of the BH4 domain of the anti-apoptotic Bcl-xL protein fused to the protein transduction domain of the HIV-1 TAT protein, was able to cross the BBB and protect astrocytes in vivo in a mouse model of ALS, after systemic administration [85]. Although lacking specificity towards astrocytes, this approach resulted promising and highlighted features of the delivery system that are shared by other peptides derived from different viral glycoproteins [193,203,204]. More recently, a homing peptide, named AS1 and showing high affinity and specificity for the astrocytes, was discovered during a phage display study [205].…”
Section: Peptide-based Deliverymentioning
confidence: 99%
“…RVG peptide containing nine arginine residues to the carboxy terminus was reported as a useful siRNA carrier to the brain across the BBB via systemic administration, and the combination of RVG peptide with various carriers for drug and gene delivery to the CNS was further reported [ 32 , 33 , 34 , 35 ]. However, perhaps because of the difference in molecule size, polyplexes of RVG peptide and pDNA have not been well reported without modifications for condensation or stability of polyplexes [ 36 , 37 , 38 ]. In this study, a ternary complex was prepared using PEGylated polyethyleneimine (PEG-PEI) to improve the in vivo stability of the polyplex.…”
Section: Introductionmentioning
confidence: 99%